New Media dan Demokrasi: Menimbang Peluang - Prajarto, Nunung (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2006)
New media is the future of communication. This statement underlines the potential contribution of new media, as the development of communication technology promises. Some who worry about the negative impacts of new media, lead to reactive instead of proactive and minimize the usage. Others, who are convinced by the potential power of new media in enhancing democracy keen to make the best use of it. This article highlights this controversy.